Computer Aided Full Arch Restoration by Means of One-Piece Implants and Stackable Guide: A Technical Note - Mattia Manfredini; Pier Paolo Poli; Carlo Maiorana; Federica Eugenia Salina; Marco Tandurella; Mario Beretta (Dentistry Journal, 2023)
This technical note aims to present a recently developed computer-guided protocol characterized by titanium-reinforced stackable surgical guides during post-extractive implant placement and subsequent immediate loading. A full maxillary edentulism was rehabilitated with one-piece implants, starting from a pre-existing removable denture. 3D digital scans of the removable denture and upper and lower arches were performed. On this basis, a prototype with ideal esthetic and functional outcomes was realized and replicated into a custom-made radiological stent with markers. The superimposition of STL and DICOM files allowed virtual planning of one-piece implants in the ideal prosthetically driven position. The stackable guides, composed of a fixed base template and additional removable components, were then realized. The fixed template, initially secured with anchor pins to the bone, was no longer removed. The removable components, which were screwed to the base template, were used to perform implant surgery and immediate prosthetic loading. No surgical complications occurred, the implants achieved a minimum insertion torque of 35 Ncm, and immediate prosthetic loading was performed. The base template allowed for the maintenance of a fixed reference during the entire workflow, improving the transition between the digital project, the surgical procedure, and the prosthetic rehabilitation.